Development of ADDIE-based transformative learning technology textbooks oriented towards stylistic analysis of novels for PBSI students: testing validity, practicality, and effectiveness - Fujiastuti, Ariesty; Wirawati, Denik (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
The rapid advancement of digital technology over the past decade has significantly reshaped the higher education landscape, requiring students to develop critical, reflective, and adaptive thinking skills aligned with transformative learning principles. Despite this shift, the implementation of technology-supported transformative learning remains constrained by the limited availability of instructional resources that systematically integrate cognitive, affective, and behavioral dimensions of learning transformation. Addressing this gap, this study aimed to develop a Transformative Learning Technology textbook grounded in the ADDIE instructional design model and oriented toward stylistic analysis of novels. The textbook was designed to serve as a systematic, relevant, and practical learning resource for undergraduate students in Indonesian Language and Literature Education. This study employed a Research and Development (R&D) approach, with data collected through questionnaires, classroom observations, interviews, and expert evaluations. The validation process involved media experts, subject-matter experts, and prospective users to assess the feasibility, clarity, and instructional relevance of the textbook. The results of expert reviews and student evaluations indicated that the developed textbook achieved ratings ranging from good to very good and was considered appropriate for instructional use. Furthermore, effectiveness testing demonstrated a statistically significant improvement in students' creativity in developing learning technologies (p = 0.003 < 0.05). Overall, the findings suggest that the proposed textbook effectively supports technology-based transformative learning in higher education, particularly in facilitating novel stylistics analysis, and contributes to the development of innovative and reflective learning practices.